Understanding the economy : an introduction to macroeconomic theory - Croome, David R.; Robinson, J. N. (London : Weidenfeld and Nicolson, 1972)
This book is almost exclusively concerned with the first stage of macroeconomic understanding; namely it represents a general theoretical framework which may be useful in examining many countries, or different periods of economic history. In this book macroeconomic theory is developed by means of s model-building process which in the first place considers the behavior of a hypothetical economy showing only the essential features abstracted from an actual economy. After the behavior of this simple economy has been examined the complications are added one by one until the book deals with an economy much more like that of the united Kingdom and other developed countries. This process has the advantage that essential points are not obscured by inessential details and hence can be more easily understood. The book is designed to provide an introduction to macroeconomics for students who have previously studied little or no economics.
Includes bibliographical references and index.
rpm 12/07/2017
Loans
Keywords: Macroeconomics